Four Past Midnight - King, Stephen (Hodder & Stoughton, 1991)
A collection of four stories on the theme of 'midnight', the moment when the familiar world gives way to an alternative reality, and a new and terrifying world is revealed.
English Fiction.
Keywords: Short stories -- Horror tales